(untitled) (Journal of Education and Development, 2017)
Global higher education is experiencing a myriad of challenges that impact the performance and application of education throughout the world. Globalization is a force that encompasses the virtual economy and how knowledge and information are shared and used. Higher education is seen as the primary vehicle for nations to improve the economic conditions for citizens in this new economy. Concurrently, technology has impacted the ability of higher education to respond the multiple difficulties of virtual learning, increased communication efficiency and how to respond to the anytime, anywhere learning demands. Global higher education continues to develop and evolve and global leaders should recognize the essential mission of global higher education to the creation, exchange and implementation of knowledge in a global marketplace.